Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Disiplin Kerja Pegawai Pada Kantor Kelurahan Bojong Rawalumbu - Febri Dwiyanti; Sugeng Suroso; Ery Teguh Prasetyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research was used to measure the influence of leadership style and organizational culture on the work discipline of Bojong Rawalumbu District office employees. This research is quantitative research whose object is used by employees of the Bojong Rawalumbu District office. This research uses a nonprobability sampling technique with a saturated sample method. The number of samples used in this research was 58 respondents. Data processing and hypothesis testing using SPSS 27 software. The research results show that Leadership Style (X1) has a partial effect on Work Discipline (Y). Organizational Culture (X2) partially influences Work Discipline (Y). Simultaneous test results show that Leadership Style (X1) and Organizational Culture (X2) simultaneously influence Work Discipline (Y).